Playfulness in Children with Limited Motor Abilities When Using a Robot. (2nd July 2016) - Ríos-Rincón, Adriana M.; Adams, Kim; Magill-Evans, Joyce; Cook, Al
ABSTRACT: Aims: Children with limited gross motor and manual abilities have fewer opportunities to engage in free play. We investigated the effect of a robotic intervention on the playfulness of children with cerebral palsy (CP). Methods: We used a partially nonconcurrent multiple baseline design with four children and their mothers. Children were classified in level IV or V on the Gross Motor Function and Manual Ability Classification Systems. The intervention was the availability of an adapted Lego robot during a 15-min free play session between the child and mother. There were two sessions per week for about 14 weeks. Playfulness was measured using the Test of Playfulness. Results: Statistical comparisons using the 2 SD band and X-moving range chart methods revealed that all the children's levels of playfulness increased significantly while they played with the robot. Comparison of baseline and follow-up phase indicated that three children had retention of improved level of playfulness. Conclusion: Play with adapted Lego robots increased the level of playfulness in all four children during free play with their mothers. The findings have implications for providing children with limitations in motor abilities opportunities for free play with family and friends.